2021
DOI: 10.1111/1462-2920.15837
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of key atmospheric volatile organic compounds by the marine heterotrophic bacterium Pelagibacter HTCC1062 (SAR11)

Abstract: Plants and phytoplankton are natural sources of the volatile organic compounds (VOCs) acetone and isoprene, which are reactive and can alter atmospheric chemistry. In earlier research we reported that, when co-cultured with a diatom, the marine bacterium Pelagibacter (strain HTCC1062; 'SAR11 clade') reduced the concentration of compounds tentatively identified as acetone and isoprene. In this study, experiments with Pelagibacter monocultures confirmed that these cells are capable of metabolizing acetone and is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 73 publications
(139 reference statements)
0
14
0
Order By: Relevance
“…Despite the differences in the environmental setting among stations (Table S1, Lasbleiz et al, 2016) the contribution of SAR11 to the total cells and to active cells appeared to be relatively constant. This is likely due to their successful adaptation to oligotrophic waters and to their capacity to efficiently take up organic substrates, among those some phytoplankton‐derived metabolites, such as very labile volatile molecules (Moore et al, 2020, 2022; Sun et al, 2011), while other taxa may favour high‐molecular‐weight DOM utilization (Malmstrom et al, 2005) as reported during the present cruise (Fourquez et al, 2016; Landa et al, 2018). So far, no known siderophores or heme uptake genes have been observed in SAR11 genomes (Hogle et al, 2016), suggesting that the success of SAR11 in these Fe‐limited waters could further be due to other specific strategies related to uptake, storage and utilization of this limiting micronutrient (Beier et al, 2015; Debeljak et al, 2019; Sun et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the differences in the environmental setting among stations (Table S1, Lasbleiz et al, 2016) the contribution of SAR11 to the total cells and to active cells appeared to be relatively constant. This is likely due to their successful adaptation to oligotrophic waters and to their capacity to efficiently take up organic substrates, among those some phytoplankton‐derived metabolites, such as very labile volatile molecules (Moore et al, 2020, 2022; Sun et al, 2011), while other taxa may favour high‐molecular‐weight DOM utilization (Malmstrom et al, 2005) as reported during the present cruise (Fourquez et al, 2016; Landa et al, 2018). So far, no known siderophores or heme uptake genes have been observed in SAR11 genomes (Hogle et al, 2016), suggesting that the success of SAR11 in these Fe‐limited waters could further be due to other specific strategies related to uptake, storage and utilization of this limiting micronutrient (Beier et al, 2015; Debeljak et al, 2019; Sun et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…is the only subclade with Fe regulatory mechanisms for adaptation to Fe limitation (Grote et al, 2012;Smith et al, 2010). Subclade Ia is also adapted to respond to phytoplankton-derived one-carbon and volatile organic compounds (Halsey et al, 2017;Moore et al, 2020Moore et al, , 2022Sun et al, 2011). Its low requirements and efficient utilization of inorganic Fe and organic substances may explain the success of this SAR11 Ia.1 clade in the region.…”
Section: Resultsmentioning
confidence: 99%
“…This has been accompanied by sparse but solid evidence 20,21,34 for the presence in marine waters of isoprene-degrading bacteria belonging mainly to the phylum Actinobacteria. Two more recent studies 24,35 suggested that members of the ubiquitous SAR11, the most abundant bacterial clade in the ocean, can also consume isoprene, but this was mainly based on indirect evidence and requires confirmation. Our k loss did not show any significant correlation with the total bacterial abundance (Table 1).…”
Section: Variability Of Isoprene Loss Rate Constants In the Open Oceanmentioning
confidence: 99%
“…Chemical oxidation is taken for granted 18 because of isoprene's high reactivity 19 , but it has never been measured. Likewise, the occurrence of isoprene-degrading bacteria in seawater has been demonstrated 20,21 and a significant microbial sink has been suggested [22][23][24] , but it has not been experimentally confirmed, let alone measured, in natural conditions including natural concentrations.…”
mentioning
confidence: 99%
“…In addition to vitamin transfer, symbiotic bacteria of algae can, among other tasks, take up primary metabolites from algae as dissolved organic matter (DOM) and supply inorganic nutrients [117][118][119]. It might therefore be that part of the VOCs are taken up by the bacteria in the culture as DOM [120,121], as has been shown, e.g., for the volatile isoprene [122,123]. In addition, compounds released by the bacteria and taken up by mixotrophic P. cordatum may influence the algal VOC production.…”
Section: Function Of the Identified Volatilesmentioning
confidence: 99%